2022
DOI: 10.3390/cancers14061415
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation of the Pleural Cavity: A Review on Pathogenesis, Diagnosis and Implications in Tumor Pathophysiology

Abstract: Pleural effusions are a common respiratory condition with many etiologies. Nonmalignant etiologies explain most pleural effusions and despite being nonmalignant, they can be associated with poor survival; thus, it is important to understand their pathophysiology. Furthermore, diagnosing a benign pleural pathology always harbors the uncertainty of a false-negative diagnosis for physicians and pathologists, especially for the group of non-specific pleuritis. This review aims to present the role of the inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…For instance, acute respiratory distress syndrome (ARDS) and acute lung injury (ALI) are inflammatory pulmonary disorders where damage to the alveolar–capillary barrier leads to the release of neutrophil granules and oxidative injury [ 41 , 42 ]. Additionally, some of the causes of pleurisy, a condition where the layers separating the lungs from the chest are injured, are also related to inflammation [ 43 ]. Excessive and chronic inflammation in the lungs can be life-threatening, given the vital role of this organ.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, acute respiratory distress syndrome (ARDS) and acute lung injury (ALI) are inflammatory pulmonary disorders where damage to the alveolar–capillary barrier leads to the release of neutrophil granules and oxidative injury [ 41 , 42 ]. Additionally, some of the causes of pleurisy, a condition where the layers separating the lungs from the chest are injured, are also related to inflammation [ 43 ]. Excessive and chronic inflammation in the lungs can be life-threatening, given the vital role of this organ.…”
Section: Resultsmentioning
confidence: 99%
“…Blintcliffe et al suggested that pleurodesis may be the last choice in benign pleural or suspected malignant effusion treated with an indwelling pleural catheter without observed benefits [ 86 ]. At the same time, in vitro observations suggest that maintaining an ongoing pleural effusion may help cancer cells to survive and develop [ 87 , 88 ].…”
Section: Talc: the Potential Link Between Mesothelial Hyperplasia And...mentioning
confidence: 99%
“…IL-6 stimulates the production of extracellular matrix components, such as collagen, leading to fibrotic tissue deposition. Excessive fibrosis can impair organ function and compromise peritoneal dialysis efficiency, and elevated levels of IL-6 have been associated with poor prognosis in peritoneal fibrosis [ 66 , 67 ]. In peritoneal dialysis-associated peritonitis, inflammatory factors and fibrotic mediators reduce the secretion of decorin by peritoneal mesothelial cells (PMCs), causing excessive deposition of fibronectin secreted by PMCs and fibrosis [ 68 70 ].…”
Section: Introductionmentioning
confidence: 99%